Bouldering Psychotherapy for Mental Health in Brazil: Preliminary Evidence from a Mixed-Methods Controlled Study - Pedro Carvalho Frulane de Souza; Tatiana Arenas Mora; Tiago Arruda Sanchez; Erick Francisco Quintas Conde (International Journal of Environmental Research and Public Health, 2026)
Previous studies have shown that Bouldering Psychotherapy (BPT), an emerging integrative intervention combining bouldering with psychotherapeutic techniques, may promote improvements in mental health and well-being. This pilot study aimed to examine the effects of BPT on symptoms of depression and anxiety in a Brazilian population and explore participants’ perceptions of its psychological and social impacts. Eleven participants completed an eight-week BPT program and were compared with a matched control group. Symptoms of anxiety and depression were assessed before and after the intervention. Qualitative data were collected through semi-structured interviews and analyzed using word-frequency analysis and reflexive thematic analysis. The BPT group showed a significant reduction in depressive symptoms (p = 0.015, d = 0.66) and a marginally non-significant reduction in anxiety symptoms (p = 0.059, d = 0.44). The qualitative findings indicated perceived improvements in psychological well-being, emotional regulation, self-awareness, social connectedness, and psychological skills. Participants also reported transferring skills and insights acquired during the program to everyday life. Overall, the findings suggest that BPT may improve mental health, particularly depressive symptoms, while fostering supportive social relationships and positive psychological experiences. The results support the feasibility of adapting BPT to the Brazilian context and encourage further research on climbing-based psychotherapeutic interventions.